Análisis jurídico y doctrinario del delito de concusión de las y los asambleístas, y la punibilidad en la legislación ecuatoriana - Benitez Uchuari, Dayely Solange (2023)
The present Research Work has arisen from the interest of analyzing the crime of concussion committed by a public servant with the quality of Assemblyman and the existing proportionality between the sanction imposed and the damage caused, the initiative arises from the notable increasement in the conduct within the National Assembly and the worrying regularization which has been given today to privatize positions within the Public Administration. This tremendous problem, also known as tithes, brings with it several legal consequences, these being the injury to the proper functioning of the Public Administration and the significant and illegal decrease in the economic heritage of the victim or victims; which, in turn, limits the correct enjoyment and exercise of other fundamental rights of both the victim and his/her family, including: health, housing, education, dignified life, etc.; With this practice, the constitutionally established service to the community to which every public servant is subject is left aside, resulting in a deficient public administration; due to once a certain candidate obtains the approval and trust of the citizenry and therefore the position within the Legislative Function, he/she leaves aside the common good and prioritizes personal economic interests, which is why his/her collaborators represent a source of extra income, In other words, the profile considered ideal to work alongside the assembly member is not based on knowledge, but rather on their entire willingness to pay monthly fees in exchange for a job. The fundamental objective of the current investigation is to carry out a conceptual, doctrinal and legal study of the crime of concussion as well as the functions that an assembly member regularly performs or should perform, in order to formulate a legal criterion regarding the proportionality of the sentence; let us remember that this conduct is increasing and our legal system sanctions it with a minimum custodial sentence of 3 years with the possibility of reducing it when certain mitigating circumstances are verified, leading us to question whether this sentence is really proportional to the damage caused and fully fulfills its purposes or on the contrary, it is deficient and therefore deserving of a legal reform.